2004
DOI: 10.1177/0148607104028003142
|View full text |Cite
|
Sign up to set email alerts
|

Liver function and plasma antioxidant status in intensive care unit patients requiring total parenteral nutrition: comparison of 2 fat emulsions

Abstract: The lower increase of plasma liver enzymes and phospholipids/apo A1 ratio in the SMOF group suggest a better liver function than in the LIPOVEN group. This beneficial effect results in a higher liver mobilization and plasma levels of lipophilic antioxidants. They could, together with higher delivery of omega-3 fatty acids to peripheral tissues, contribute positively to survival rate of stressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 46 publications
4
104
2
3
Order By: Relevance
“…Recently, supplementation with fish oil is supposed to improve standard clinical therapy for chronic hyper-inflammatory diseases such as Crohn' disease [1,5] , rheumatoid arthritis [6] , cancer cachexia [7,8] , and as an adjunct therapeutic measure for trauma, injure, and sepsis [2,[9][10][11][12] . Although several studies have demonstrated the beneficial effects of omega-3 fatty acid supplementation on patient outcome or immune competence, randomized controlled clinical trials focusing on the use of parenteral fish oil are scarce [13][14][15][16][17] . The aim of this study was to assess whether parenteral supplementation of omega-3 fatty acid postoperatively improves the inflammatory and immunological function of colorectal cancer patients and their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, supplementation with fish oil is supposed to improve standard clinical therapy for chronic hyper-inflammatory diseases such as Crohn' disease [1,5] , rheumatoid arthritis [6] , cancer cachexia [7,8] , and as an adjunct therapeutic measure for trauma, injure, and sepsis [2,[9][10][11][12] . Although several studies have demonstrated the beneficial effects of omega-3 fatty acid supplementation on patient outcome or immune competence, randomized controlled clinical trials focusing on the use of parenteral fish oil are scarce [13][14][15][16][17] . The aim of this study was to assess whether parenteral supplementation of omega-3 fatty acid postoperatively improves the inflammatory and immunological function of colorectal cancer patients and their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This emulsion is designed to increase the amount of n-3 fatty acids, thereby reducing the ratio of n-6 to n-3 fatty acids (in accordance with current recommended levels). 43 SMOFlipid 20% is well tolerated in infants without changing lipid peroxidation parameters, 31,44 and beneficial effects on liver function and serum triglyceride concentrations have been described. 31 …”
Section: Risks and Benefits Of Parenteral Nutritionmentioning
confidence: 99%
“…The use of early PN is quite common nowadays and its demand is rapidly increasing for the pediatric population especially in preterm neonates [17]. In this systematic review, the benefits and harmful effects of lipid emulsion has been described on the account of clinical outcomes, by the introduction of lipid in early and late life days.…”
Section: Discussionmentioning
confidence: 99%